A prospective study to assess the safety and expulsion rate of copper T380A in immediate post-partum period during caesarean section - Bedi, Preet Kamal; Guliani, Manjit Singh; Bala, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Immediate post-partum IUCD insertion deserves great attention as it can provide immediate contraception and prevents repeated unintended pregnancies. Increasing number of women undergoing elective cesarean section due to repeat cesarean section need effective long term contraception to allow them recuperate from surgery and for reliable means of child spacing. The postpartum insertion of an IUCD provides a convenient opportunity for the woman to receive IUCD services. This is particularly important for women who have limited access to medical care. The objective of this study was to assess the safety in terms of perforation, pain, bleeding, foul smelling vaginal discharge and expulsion rates at 6 weeks follow up and reasons for removal/discontinuation willingness to continue when CuT380A is inserted immediately after C-section deliveries. Methods: The present study was conducted at Bebe Nanaki Mother and Child Care Hospital, Govt. Medical College, Amritsar, between period February 2014 to June 2015, on 200 cases undergoing caesarean section delivery willing for IUCD insertion and who fulfilled the medical eligibility criteria and had no contraindications for PPIUCD and patients were followed up at 6 weeks. Results: A total of 200 women underwent postpartum intracaesarean insertion of copper T 380A. And 16 women lost to follow up. Acceptance was more in the multigravida. The mean age of women included in the study was 25.65±2.42 years. Most common post-insertion complication observed in the immediate postoperative period was excessive bleeding. The common adverse events observed during follow-up of 6 weeks were menstrual complaints, excessive vaginal discharge and persistent pelvic pain. At the end 6 weeks, there were 6 expulsions, 4 removals, and gross cumulative expulsion, removal, failure and continuation rates of 3.2%, 2.2% and 5.4%, respectively. Conclusions: Inserting CuT380A after placental delivery during cesarean section is safe and effective, has high retention rate. The expulsion rate was not high, and can be further reduced with practice. The method may be particularly beneficial in our setting where women do not come for post natal contraception counseling and usage. The government needs to develop strategies to promote PPIUCD by increasing awareness, by arranging trainings among healthcare providers.